If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 11 = 26 Reorder the terms: 11 + 6x = 26 Solving 11 + 6x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 6x = 26 + -11 Combine like terms: 11 + -11 = 0 0 + 6x = 26 + -11 6x = 26 + -11 Combine like terms: 26 + -11 = 15 6x = 15 Divide each side by '6'. x = 2.5 Simplifying x = 2.5
| 4x+12=-4 | | 4x+5y=100 | | (3b+7)+(8b+3)= | | 3=3x-15 | | 2x+50=12x-10 | | -63+46w=25w-147 | | 7/c-2/c=4/c-1 | | z^2-5iz-4=0 | | 15/2p-13/2p | | 23h-89=63+42h | | 5ln(4x-2)-16=9 | | x^4+11x^3-44=0 | | 16x-19=113-6xz | | 63d-44=-140+47d | | 3x^2+x-1900=0 | | 63d-44=140+47d | | -21+6x=33+9x | | 12-3x/x^2-8x+16 | | 5(g-2)+g=6g-24 | | x=log(3)15 | | x^4+11x^2-44=0 | | x^2+11x^2-44=0 | | 14j-53=73+32j | | 2n/n^2-3n | | -14p+51=57p+23 | | t-1/t^2+t | | 75+21k=19+29k | | -80=b-91 | | x(7-x)+2whenx=-4 | | 20=t-70 | | 4(x+8)-7whenx=8 | | lg(x+3)+lg(1-x)=lg(4x+8) |